Inventarization Epiphytic Mosses in Hutan Lumut Area âDataran Tinggi Yangâ, Wildlife Preserve Argopuro Mountain - Rahardian, Galen; Prakosa, Gayut Widya; Anas, Aswar; Hidayatullah, Alhabsy; Hasan, Ahmad Zainul (Biotropika: Journal of Tropical Biology, 2017)
Mosses are group of non-vascular plant, small size, and able to growth in many substrates. Epiphytes are organism witch growth at wood surface of living plant. Epiphytic mosses has some advantages, there are out ofÂ Â range from terestial organism and to get more optimaly sun light. One of place which has suitable conditions for this research is in Wildlife Preserve âDataran Tinggi Yangâ, Argopuro Mountain. This research purpose to get known about species of epiphyte mosses and morphological characteristic each species of epiphytic mosses in Wildlife Preserve âDataran Tinggi Yangâ, Argopuro Mountain. The result of identification and characterization obtained 17 families and 25 species of epiphytic mosses. The main characteristic of mosses are leaf position, leaf form, Â and leaf costa.